A scoping review of how exposure to urban violence impacts youth access to sexual, reproductive and trauma health care in LMICs - Gill Green; Alison Swartz; Doreen Tembo; Diane Cooper; Asha George; Richard Matzopoulos; Andrea Fachel Leal; Cristiane Cabral; Regina Barbosa; Daniela Knauth (Taylor & Francis Group, 2023)
ABSTRACTViolence in the community can impact access to health care. This scoping review examines the impact of urban violence upon youth (aged 15-24) access to sexual and reproductive health and trauma care in Low and Middle Income Countries (LMICs). We searched key electronic health and other databases for primary peer-reviewed studies from 2010 through June 2020. Thirty five of 6712 studies extracted met criteria for inclusion. They were diverse in terms of study objective and design but clear themes emerged. First, youth experience the environment and interpersonal relationships to be violent which impacts their access to health care. Second, sexual assault care is often inadequate, and stigma and abuse are sometimes reported in treatment settings. Third is the low rate of health seeking among youth living in a violent environment. Fourth is the paucity of literature focusing on interventions to address these issues. The scoping review suggests urban violence is a structural and systemic issue that, particularly in low-income areas in LMICs, contributes to framing the conditions for accessing health care. There is a gap in evidence about interventions that will support youth to access good quality health care in complex scenarios where violence is endemic.